Glycosaminoglycans and syndecan-4 are involved in SDF-1/CXCL12-mediated invasion of human epitheloid carcinoma HeLa cells - Brule, Severine; Friand, Véronique; Sutton, Angela; Baleux, Françoise; Gattegno, Liliane; Charnaux, Nathalie (Biochimica et biophysica acta, 2009)
In addition to their physiologic effects in inflammation and angiogenesis, chemokines are involved in cancer pathology. The CXC-chemokine stromal cell-derived factor-1 (SDF-1)/CXCL12 mediates its biological activities through activation of G protein-coupled receptor CXCR4 and binds to glycosaminoglycans (GAGs). Using Bio-coat cell migration chambers, specific antagonists, flow cytometry and RNA interference, we evaluate the involvement of heparan sulfate proteoglycans (HSPG) in the SDF-1/CXCL12-induced invasion of human cervix epitheloid carcinoma HeLa cells. The SDF-1/CXCL12-induced cell invasion is dependent on CXCR4. Furthermore, Protein Kinase C delta (PKC δ) and c-jun NH2-terminal kinase/stress-activated protein kinase (JNK/SAPK) are implicated in this event, but not extracellular signal-regulated kinase (ERK) 1/2. Moreover, the invasion of HeLa cells induced by SDF-1/CXCL12 was dependent on matrix metalloproteinase-9 (MMP-9). The pre-incubation of HeLa cells with heparin or with anti-heparan sulfate antibodies or with β- d-xyloside inhibited SDF-1/CXCL12-mediated cell invasion. Furthermore, the down-regulation of syndecan-4, a heparan sulfate proteoglycan, decreased SDF-1/CXCL12-mediated HeLa cell invasion. GAGs, probably on syndecan-4, are involved in SDF-1/CXCL12-mediated cell chemotaxis. These data suggest that targeting the glycosaminoglycan/chemokine interaction could be a new therapeutic approach for carcinomas in which SDF-1/CXCL12 is involved.